Optimizing the Performance of Bhabinkamtibmas Polres Tegal Using Personal Smart Tools in Maintenance of Kamtibmas Presisi - Yunita, Alvira (Advances in Police Science Research Journal, 2024)
Since 2020, crime events have persisted and increased, making the societies in the Tegal Police Legal Area anxious and afraid. In order to strengthen the performance of upholding security and public order, particularly by strengthening Bhabinkamtibmas by personal smart tools, the Tegal Polres implements a predictive policing pattern based on the 16 priority programs of the National Police Chief. The goals of this research was to ascertain the degree to which Bhabinkamtibmas Polres Tegal has implemented personal smart tools in maintaining Precision Kamtibmas. The data for this qualitative field research were gathered from a variety of sources under the Tegal Police’s purview through interviews, observations, document analysis, and focus groups discussions (FGD). Which is reviewed with the concept of optimizing the concept of performance, the concept of Bhabinkamtibmas, the concept of personal smart tools, and the concept maintenance of Kamtibmas Presisi. The theories used in this research are management theory POAC, SDM theory 5M, and SWOT theory. Performance Bhabinkamtibmas was analyzed using P-O-A-C management theory and optimizing Bhabinkamtibmas were analyzed using The 5 M SDM theory. Factors that affect the implementation of personal smart tools by Bhabinkamtibmas were analydes using SWOT theory. The findings of this research suggest that in order to keep maintain and order in their sphere of influence, Bhabinkamtibmas must optimize performance in the implementation of personal smart tools. This is aligned with the Police’s Precision Transformation, particularly with regard to the fifth Program, Strengthening the performance of Public Order and Order Maintenance through Implementation of Personal Smart Tools. In order to be able to educate the societies about the Kamtibmas situation and establish themselves as a village information hub, Bhabinkamtibmas officials must be able to perform better when implementing personal smart tools.